Teachers’ Interactive Decisions and Personal Development: The Basis and Factors - Hartati Suryaningsih; Desi Herayana (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This research aims to recognize the factors triggering and foundations affecting teachers’ interactive decisions related to teachers’ personal development. Interactive decisions as teachers’ reaction to an unexpected situation during teaching and learning activities. The participants in this study are 3 (three) English course teachers. The participants were chosen using purposive sampling. The data were collected through semi-structured interviews. The data then were analyzed using Gomm’s thematic analysis. The results showed that the factors triggering teachers’ interactive decisions were teachers’ assumptions, teachers’ expectations – students’ lack of cooperation, and technical problems; the foundations of the interactive decisions were teacher’s experience, students’ needs, and class management. These findings indicate that making an interactive decision is a complex process. Many situations may trigger it, and teachers have to cope with it instantly without preparation. These unexpected situations require teachers’ quick thinking and reaction which are based on and enrich their personal development.